Teaching Orthophony in Primary Education by means of theatrical techniques - Katerina Diakoumopoulou (3ο Συνέδριο της Ένωσης Εκπαιδευτικών Μουσικής Αγωγής Πρωτοβάθμιας Εκπαίδευσης «Η συμβολή του εκπαιδευτικού υλικού στη σχολική πράξη: θεωρία και εφαρμογή στη Μουσική Εκπαίδευση»., 2009)
The aim of the lab was to combine the theory of orthophony science with the empirical art of theatre education, just as it should be taught in primary education. Blending the science of phonetics and theatrical art constitutes an attractive methodology for the group to which it is addressed (age of reference 8-12 years old). The lab particularly focused on the practice –by means of theatrical games- of the theoretical base of Orthophony. Breathing: Benefits and ways of achieving breathing through the diaphragm. Vocalization: Structure and practice of phonetic organs, which are the organs that produce the sound. Articulation: Proper formation of phonemes and their practice. Those participating in the lab had the opportunity to learn the principles of Orthophony first on a theoretical level and then, on an empirical one; the final stage aimed at creating collective exercises, and its ulterior purpose was to apply them at school.